KEHIDUPAN SOSIAL MASYARAKAT PASCA PANDEMI COVID-19 DI DESA HATUNGUN KECAMATAN HATUNGUN KABUPATEN TAPIN - Kurnia Oktaviani; Fuad Muhajirin Farid; Syahrial Shaddiq (RAGAM: Journal of Statistics & Its Application, 2023)
COVID-19 is a virus that can be transmitted to everyone caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The World Health Organization (WHO) has officially declared COVID-19 a pandemic because the spread of this virus is very fast. The COVID-19 pandemic itself has been going on for more than 2 years and has had a real impact on the people of Indonesia. The three main impacts that are felt by the community are social interaction between communities, community economic activities and people's lifestyles. This study aims to find out and understand social interaction between communities, community economic activities and the lifestyle of the people in Hatungun Village during the post-COVID-19 pandemic. Data collection techniques used in this study using observation, interviews and documentation. The data analysis itself uses qualitative descriptive statistics. The results obtained state that there are no obstacles in social interaction between communities during the post-COVID-19 pandemic, in economic activity there are constraints that are still being felt today as a result of the paralysis of various sectors, especially in the economic sector which causes the price of basic commodities to increase while income decreases and spending online there is nothing to change a person's lifestyle if the person is wise in reacting to it.Keywords:    Social Society, COVID-19 Pandemic, Tapin District.